Neuronal density in the brain cortex and hippocampus in Clsnt2-KO mouse strain modeling autistic spectrum disorder - I. N. Rozhkova; S. V. Okotrub; E. Yu. Brusentsev; E. E. Uldanova; E. А. Chuyko; T. V. Lipina; T. G. Amstislavskaya; S. Ya. Amstislavsky (Вавиловский журнал генетики и селекции)
Autistic spectrum disorders (ASD) represent conditions starting in childhood, which are characterized by difficulties with social interaction and communication, as well as non-typical and stereotyping models of behavior. The mechanisms and the origin of these disorders are not yet understood and thus far there is a lack of prophylactic measures for these disorders. The current study aims to estimate neuronal density in the prefrontal cortex and four hippocampal subfields, i. e. СA1, СA2, СA3, and DG in Clstn2-KO mice as a genetic model of ASD. In addition, the level of neurogenesis was measured in the DG area of the hippocampus. This mouse strain was obtained by a knockout of the calsinthenin-2 gene (Clsnt2) in C57BL/6J mice; the latter (wild type) was used as controls. To estimate neuronal density, serial sections were prepared on a cryotome for the above-mentioned brain structures with the subsequent immunohistochemical labeling and confocal microscopy; the neuronal marker (anti-NeuN) was used as the primary antibody. In addition, neurogenesis was estimated in the DG region of the hippocampus; for this purpose, a primary antibody against doublecortin (anti-DCX) was used. In all cases Goat anti-rabbit IgG was used as the secondary antibody. The density of neurons in the CA1 region of the hippocampus was lower in Clstn2-KO mice of both sexes as compared with controls. Moreover, in males of both strains, neuronal density in this region was lower as compared to females. Besides, the differences between males and females were revealed in two other hippocampal regions. In the CA2 region, a lower density of neurons was observed in males of both strains, and in the CA3 region, a lower density of neurons was also observed in males as compared to females but only in C57BL/6J mice. No difference between the studied groups was revealed in neurogenesis, nor was it in neuronal density in the prefrontal cortex or DG hippocampal region. Our new findings indicate that calsyntenin-2 regulates neuronal hippocampal density in subfield-specific manner, suggesting that the CA1 neuronal subpopulation may represent a cellular target for earlylife preventive therapy of ASD.